Pembentukan Posyandu Remaja Sebagai Upaya Peningkatan Pengetahuan dan Kualitas Kesehatan Remaja di Dusun Dingkikan, Sedayu, Bantul - Suwarjono, Mulyanti (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Adolescence is a period of transition from childhood to adulthood; this triggers the emergence of complex problems due to the risky behavior they do. Dingkikan is one of the hamlets in the working area of PUSKESMAS Sedayu 2, with a total of 177 adolescents. The results found that 28.6% of adolescents in Dusun Dingkikan had a smoking habit, 66.7% did not routinely do health checks, 28.57% did not understand the dangers of smoking, 41.3% did not know about reproductive health, 84.1% thought discussing reproductive health was inappropriate, 49.2% did not know about free sex behavior, 57.1% did not know about sexually transmitted diseases, and 17.5% experienced chronic malnutrition. Youth POSYANDU is one solution to overcome the problems in adolescents and an effort to prepare them as a generation of creative planning and have good health insight. The series of activities carried out in the context of establishing the Youth POSYANDU of Dingkikan is to socialize it, hold youth POSYANDU training, form youth health cadres, first aid training, counseling on clean and healthy living behavior, counseling on mosquito larvae monitoring, anemia, family medicinal plants, reproductive health, nutrition, drugs, and non-communicable diseases. The Head of Argodadi Village officially appoints youth health cadres who have received briefing and further training. The Dingkikan Youth POSYANDU is held every month accompanied by community leaders, health cadres, the village government, and the PUSKESMAS Sedayu 2